European Productivity, Innovation and Competitiveness : The Case of Italy - Tiffin, Andrew (IMF Working Papers; Working Paper ;, 2014)
In Italy, price-based competitiveness measures are not always an accurate predictor of trade outcomes. This paper offers a more comprehensive assessment of Italian competitiveness, focusing on the role of innovation and the evolution of Italy's export market share. Overall, Italy maintains a high-quality export mix, and the adaptability of small-scale specialized firms is still a source of strength. But, small firm size is becoming less of an asset, and even the most innovative sectors are weighed down by the structural barriers that have depressed productivity more broadly. Italy's future competitiveness will depend on full implementation of a comprehensive structural-reform agenda.